Justice as A Law Sacrament: Measuring Justice in Pancasila Philosophy - Yosep Copertino Apaut; Randy Vallentino Neonbeni (International Journal of Social Service and Research, 2023)
Indonesia as a plural country with a diversity of ethnicities, religions, races, customs, cultures, regional languages, will really rely on a single nation principle, namely Pancasila with the logical consequence that every aspect of its life will be governed by Pancasila which is chaired by the state through its tool, namely the government. fully sovereign. This means that all complex life of society is entrusted to the State, including in the field of law to achieve essential justice. In this regard, the state is obliged to carry out the orders of Pancasila through the constitution, which is used as a guideline and benchmark in every practice of state administration, including aspects of law enforcement that are just for all Indonesian people.